2019
DOI: 10.1371/journal.pntd.0007434
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting chronic conditions for fatal outcome among SFTS patients: An observational Cohort Study

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease that is caused by a novel bunyavirus SFTSV. Currently our knowledge of the host-related factors that influence the pathogenesis of disease is inadequate to allow prediction of fatal outcome. Here we conducted a prospective study of the largest database on the SFTS patients, to identify the presence of comorbidities in SFTS, and estimate their effect on the fatal outcome. Among 2096 patients eligible for inclusion, we identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…SFTSV infection has been one of the most important public health issues in endemic areas because of its high case fatality ratio, which was reported to be 10–20% in China and South Korea [ 2 , 3 ] and 27–31% in Japan [ 4 , 5 ]. The poor prognostic backgrounds for SFTS include advanced age, male sex [ 6 ], and underlying diseases, such as malignancies, diabetes mellitus, chronic viral hepatitis, and chronic obstructive pulmonary disease [ 5 , 7 ]. In addition, patients with central nervous system manifestations [ 4 , 8 ], high levels of alanine aminotransferase (ALT), lactate dehydrogenase (LDH), and creatine kinase (CK) [ 8 ], renal dysfunction [ 9 ], coagulopathy, high level viremia, and hypercytokinemia were reported to show poor prognosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…SFTSV infection has been one of the most important public health issues in endemic areas because of its high case fatality ratio, which was reported to be 10–20% in China and South Korea [ 2 , 3 ] and 27–31% in Japan [ 4 , 5 ]. The poor prognostic backgrounds for SFTS include advanced age, male sex [ 6 ], and underlying diseases, such as malignancies, diabetes mellitus, chronic viral hepatitis, and chronic obstructive pulmonary disease [ 5 , 7 ]. In addition, patients with central nervous system manifestations [ 4 , 8 ], high levels of alanine aminotransferase (ALT), lactate dehydrogenase (LDH), and creatine kinase (CK) [ 8 ], renal dysfunction [ 9 ], coagulopathy, high level viremia, and hypercytokinemia were reported to show poor prognosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preexisting chronic comorbidity is also an attribute that should be considered, since a large part of SFTS patients were the elderly and frequently afflicted by various underlying conditions which conferred an increased risk of adverse outcomes following infection. Previous studies revealed that adverse outcomes of SFTS patients were associated with comorbidities (Deng et al, 2013;Xu et al, 2018;Zhang et al, 2019), which were specifically identified to be diabetes mellitus (DM), chronic virus hepatitis (CVH), and 1 https://is.kdca.go.kr 2 https://www.niid.go.jp chronic obstructive pulmonary diseases (COPD) in one study (Zhang et al, 2019). Up to now, no studies in analyzing the risk of SFTS mortality have ever tried to disentangle the effect from age, sex, or comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with that of Zhang who insisted underlying disease increases the risk of death (OR = 1.631; p < .001). 8 In Zhang's study, chronic viral hepatitis also increased the risk of death (OR = 2.006; p = .007). It is not uncommon for chronic viral hepatitis to be combined with other viral infections, 9 but there have been few reports of chronic viral hepatitis co‐infection with SFTSV.…”
Section: Discussionmentioning
confidence: 92%